INTERNET GOVERNANCE DALAM HUBUNGAN INTERNASIONAL - Djani, Dian Triansyah; Yani, Yanyan Mochamad (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2017)
This paper aims to examine the internet setting or internet governance in contemporary international relations that are influenced by the nuances of globalization and interdependence. Setting in the field of the Internet also emerged with the development of discovery and innovation in the field of information and communication technology. Seeing the lack of understanding and international agreements related to internet governance and there is still debate about the need for an internationally regulated internet, it is interesting to examine the phenomenon of internet regulation in the context of international relations by using relevant approaches in international relations theory.Tulisan ini bertujuan untuk mengkaji Pengaturan untuk internet atau internet governance dalam hubungan internasional kontemporer yang dilingkupi oleh nuansa globalisasi dan interdependensi. Pengaturan di bidang internet juga mengemuka dengan berkembangnya penemuan dan inovasi di bidang teknologi informasi dan komunikasi. Melihat masih minimnya pemahaman dan kesepakatan internasional terkait internet governance serta masih terdapat perdebatan mengenai perlunya internet diatur secara internasional, menarik untuk diteliti fenomena pengaturan internet dalam konteks hubungan internasional dengan menggunakan pendekatan yang relevan dalam teori hubungan internasional.